Предмет: Математика,
автор: Maiklzv
Упростить sin(a-3pi/2)*cos(pi+a)
-------------------------------
1+cos(a-5pi/2)
Ответы
Автор ответа:
0
sin(a-3π/2)*cos(π+a) = - sin(3π/2-a)*(-cosa) = cosa*cosa = cos²a =
1+cos(a-5pi/2) 1+cos(5π/2-a) 1+sina 1+sina
= (1-sin²a) = (1-sina)(1+sina) = 1-sina
1+sina 1+sina
1+cos(a-5pi/2) 1+cos(5π/2-a) 1+sina 1+sina
= (1-sin²a) = (1-sina)(1+sina) = 1-sina
1+sina 1+sina
Похожие вопросы
Предмет: Химия,
автор: alinatarasova882
Предмет: История,
автор: bekenovaaana02
Предмет: Математика,
автор: gromovak334
Предмет: Биология,
автор: бутон